Impact of Infliximab and Cyclosporine on the Risk of Colectomy in Hospitalized Patients with Ulcerative Colitis Complicated by Cytomegalovirus—A Multicenter Retrospective Study. Issue 9 (5th June 2017) - Kopylov, Uri; Papamichael, Konstantinos; Katsanos, Konstantinos; Waterman, Matti; Bar-Gil Shitrit, Ariella; Boysen, Trine; Portela, Francisco; Peixoto, Armando; Szilagyi, Andrew; Silva, Marco; Maconi, Giovanni; Har-Noy, Ofir; et al.
Abstract : Background: Cytomegalovirus (CMV) is frequently detected in patients with ulcerative colitis (UC). The impact of CMV infection on the outcome of UC exacerbation remains unclear. The benefit of combining antiviral with anti-inflammatory treatment has not been evaluated yet. The aim of this study was to compare the outcome of CMV-positive hospitalized patients with UC treated with antiviral therapy either alone or combined with salvage anti-inflammatory therapy (infliximab [IFX] or cyclosporine A [CsA]). Methods: This was a multicenter retrospective study of hospitalized CMV-positive patients with UC. The patients were classified into 2 groups: antiviral—if treated with antivirals alone; combined—if treated with both antiviral and anti-inflammatory therapy. The outcomes included the rate of colectomy in both arms during the course of hospitalization and after 3/12 months. Results: A total of 110 patients were included; 47 (42.7%) patients did not receive IFX nor CsA; 36 (32.7%) received IFX during hospitalization or within 1 month before hospitalization; 20 (18.1%) patients received CsA during hospitalization; 7 (6.4%) were exposed to both IFX and CsA. The rate of colectomy was 14.5% at 30 days, 20.0% at 3 months, and 34.8% at 12 months. Colectomy rates were similar across treatment groups. No clinical and demographic variables were independently associated with the risk of colectomy. Conclusions: IFX or cyclosporine therapy is not associated with additional risk for colectomy over antiviral therapy alone in hospitalized CMV-positive patients with UC.